PENGARUH ADVERTISING DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN DENGAN DIVERSIFIKASI PRODUK SEBAGAI VARIABEL INTERVENING (Studi Pada Paguyuban Brem Mekarsari di Kecamatan Nguntoronadi Kabupaten Wonogiri) - MUH. NURHADI S. (JURNAL WIDYA GANECWARA, 2017)
The purpose of this study was to: (1) Examine and measure the effect of advertisements and distribution channels partially on product diversification Brem at the Society of Brem Mekarsari in Sub District Nguntoronadi. (2) Examine and measure the impact of advertising of distribution channels partially on sales volume Brem at the Society of Mekarsari in Sub District Nguntoronadi. (3) Know the product diversification in mediating the effects of advertisement and distribution channels to sales volume Brem at the Society of Mekarsari in Sub District Nguntoronadi. Â  The study was conducted on the Society of the District Nguntoronadi Brem in Wonogiri. The population in this study is the whole community that the District Nguntoronadi engaged in the business of making Brem made Glutinous Rice. The sample in this study were taken as many as 122 people. As an analytical tool used in the study are causal regression step. Â  The research found that there is a partial effect of advertising, and distribution channels towards product diversification. There is a partial effect of advertising, and distribution channels to sales volume Brem. There is a mediating effect of product diversification to the influence of advertising and the influence of distribution channels in the sales volume Brem. The influence of the mediating effect of product diversification towards partial advertising, which means advertising will increase product diversification employers, and increase product diversification will lead to an increase in sales value Brem. Likewise, the influence of the mediating effect of product diversification of the distribution channels, which means partial distribution channels will enhance product diversification employers, and increase product diversification will lead to an increase in sales value Brem.